2006
DOI: 10.1063/1.2382742
|View full text |Cite
|
Sign up to set email alerts
|

Growth of single-phase In2Se3 by using metal organic chemical vapor deposition with dual-source precursors

Abstract: Characterizations of InN films on Si (111) substrate grown by metal-organic chemical vapor deposition with a predeposited In layer and a two-step growth method J. Vac. Sci. Technol. A 25, 701 (2007); 10.1116/1.2740293Growth and characterization of single crystal ZnO thin films using inductively coupled plasma metal organic chemical vapor deposition Growth of single crystalline GaN thin films on Si(111) substrates by high vacuum metalorganic chemical vapor deposition using a single molecular precursor Propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…For PL spectra, the full width of the half maximum (FWHM) of the NBE line are 182, 96.5, 93.8, 87.3, and 89.4 meV, for the IS350, IS375, IS400, IS450 and IS500 ␥-In 2 Se 3 samples, respectively. The measured RT-NBE emissions at around 1.947 eV from the ␥-In 2 Se 3 films are reasonably consistent with the estimated values of previous reports, which were deduced from the low-temperature PL data by fitting to the Varshni's equation [13,14]. Our results thus indicate that epitaxial ␥-In 2 Se 3 films with strong RT-NBE emissions were grown by atmospheric MOCVD.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…For PL spectra, the full width of the half maximum (FWHM) of the NBE line are 182, 96.5, 93.8, 87.3, and 89.4 meV, for the IS350, IS375, IS400, IS450 and IS500 ␥-In 2 Se 3 samples, respectively. The measured RT-NBE emissions at around 1.947 eV from the ␥-In 2 Se 3 films are reasonably consistent with the estimated values of previous reports, which were deduced from the low-temperature PL data by fitting to the Varshni's equation [13,14]. Our results thus indicate that epitaxial ␥-In 2 Se 3 films with strong RT-NBE emissions were grown by atmospheric MOCVD.…”
Section: Resultssupporting
confidence: 92%
“…It was found that the emission at 2.145 eV becomes eminent and finally dominant while the intensities of the other three peaks decrease rapidly with increasing temperature. The three peaks located at 2.141, 2.133 and 2.114 eV became disappeared after the temperature was increased above 60 K. Therefore, the peak at 2.145 eV was attributed to free exciton emission and the other three peaks were attributed to bound excitons or defectrelated emissions [13][14][15]. Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Chemical vapor deposition (CVD) is an alternative vapor-based approach, which offers substantial flexibility, assuming the identification of suitable volatile source materials. [13][14][15] Practical constraints on reactor size, however, limit large-area deposition using this approach and material utilization may also present a problem (much of the material flowing through the system does not end up on the substrate). High substrate temperatures (>350 8C) are also often required to achieve good crystallinity in films produced using the CVD approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, all these peaks became non-evident when the film was grown at 350 1C. Furthermore, the peak of 2.14 eV is reported to result from free exciton [17], while the other two peaks at 2.13 and 2.11 eV are considered to be caused by bound excitons [18]. Temperature-dependent (20-300 K) PL measurements were also carried out for all samples.…”
Section: Resultsmentioning
confidence: 98%